Pharmacogenetic considerations for migraine therapies. (2nd November 2018) - Capi, Matilde; Gentile, Giovanna; Lionetto, Luana; Salerno, Gerardo; Cipolla, Fabiola; Curto, Martina; Borro, Marina; Martelletti, Paolo
ABSTRACT: Introduction : Migraine is a common neurological disorder with a complex pathophysiology. It has been estimated that incidence between adults of current headache disorder is about 50%. Different studies show that this condition has an important and complex genetic component in response to drug therapy. Areas covered : This review shows and summarizes the importance of the polymorphisms associated with the major antimigraine drug metabolizing enzymes. The research of bibliographic databases has involved only published peer-reviewed articles from indexed journals. Expert opinion : Pharmacogenetics is based on the identification of polymorphism and promises personalized therapy with efficacy and reduction of adverse events. The association between genotype and an altered metabolizer status could guide clinical decision to evade concomitant treatments and adverse events. The introduction of routine genetic testing could help to choose the efficacy drug on the individual and genetic profile.